Translational potential of synaptic alterations in Alzheimer's disease patients and amyloid precursor protein knock-in mice. Issue 1 (5th January 2023) - Medina-Vera, Dina; Enache, Daniela; Tambaro, Simone; Abuhashish, Ethar; Rosell-Valle, Cristina; Winblad, Bengt; Rodríguez de Fonseca, Fernando; Bereczki, Erika; Nilsson, Per
Abstract: Synaptic dysfunction is an early event in Alzheimer's disease. Post-mortem studies suggest that alterations in synaptic proteins are associated with cognitive decline in Alzheimer's disease. We measured the concentration of three synaptic proteins, zinc transporter protein 3, dynamin1 and AMPA glutamate receptor 3 in cerebrospinal fluid of subjects with mild cognitive impairment ( n = 18) and Alzheimer's disease ( n = 18) and compared the levels to cognitively and neurologically healthy controls ( n = 18) by using ELISA assay. In addition, we aimed to assess the translational potential of these synaptic proteins in two established amyloid precursor protein knock-in Alzheimer's disease mouse models by assessing the cerebrospinal fluid, hippocampal and cortical synaptic protein concentrations. Using ELISA, we measured in parallel these three proteins in cerebrospinal fluid and/or brain of 12- and 24-month-old App NL-F and App NL-G-F knock-in mice and App Wt control mice. The regional distribution and expression of these proteins were explored upon aging of the App knock-in models by quantitative immunofluorescence microscopy. Notably, we found a significant increase in concentrations of zinc transporter protein 3 and AMPA glutamate receptor 3 in cerebrospinal fluid of both patient groups compared with cognitively healthy controls. Dynamin1 concentration was significantly higher in Alzheimer's disease patients. Remarkably, patients with mild cognitive impairment who converted to Alzheimer's disease ( n = 7) within 2 years exhibited elevated baseline cerebrospinal fluid zinc transporter protein 3 concentrations compared with mild cognitive impairment patients who did not convert ( n = 11). Interestingly, similar to the alterations in Alzheimer's disease subjects, cerebrospinal fluid AMPA glutamate receptor 3 concentration was significantly higher in App NL-G-F knock-in mice when compared with wild-type controls. Furthermore, we have detected age and brain regional specific changes of the three synaptic proteins in the hippocampus and prefrontal cortex of both App NL-F and App NL-G-F knock-in mice. Notably, all the three cerebrospinal fluid synaptic protein concentrations correlated negatively with concentrations in hippocampal lysates. The elevated zinc transporter protein 3 concentrations in the cerebrospinal fluid of converter versus non-converter mild cognitive impairment patients suggests a prospective role of zinc transporter 3 in differentiating dementia patients of the biological continuum of Alzheimer's disease. The increased cerebrospinal fluid concentrations of synaptic proteins in both patient groups, potentially reflecting synaptic alterations in the brain, were similarly observed in the amyloid precursor protein knock-in mouse models highlighting the translational potential of these proteins as markers for synaptic alterations. These synaptic markers could potentially help reduce the current disparities between human and animal model-based studies aiding the translation of preclinical discoveries of pathophysiological changes into clinical research. Abstract : This paper reports significant alterations of cerebrospinal fluid synaptic proteins throughout the biological continuum of Alzheimer`s disease. The high translatability of this synaptic profile from Alzheimer animal models to patients is essential to envisage the outcome of a treatment more accurately in patients according to Medina-Vera et al. Graphical Abstract: Graphical abstract